Developing English Reading Comprehension Modules Incorporating Chinese Culture for Undergraduates in China - Ma, Xin; Lin, SiewEng (Forum for Linguistic Studies, 2025)
This study aims to develop a set of English Reading Comprehension Modules (ERCMs) to effectively promote Chinese students’ reading proficiency and enhance their knowledge of Chinese culture to promote Quality Education. The ERCMs were developed using the ASSURE Model and contain 45 reading passages about Chinese culture for primary, intermediate and advanced readers. The reading materials were validated by experts, and a pilot study with 90 undergraduates was conducted to determine the reliability of the ERCMs. Following the rigorous development of the ERCMs, a further 131 students took the pre-test and participated in the main study, using the modules at their own level of difficulty for five weeks, during which time the process and details of class were observed and documented in Classroom Observation Checklists. Then they participated in the post-test, in which six students and three teachers were interviewed. The results of the study shown varying degrees of improvement in the learners’ overall reading ability as well as in literal comprehension, reorganization and inferential comprehension. Analyses of classroom observation checklists and interview transcripts confirmed this finding. In addition, both teachers and students reported that they had learnt more about Chinese culture through the ERCMs. We hope that the ERCMs can be used as supplementary materials to improve students’ English reading comprehension and Chinese cultural literacy